Performance of potato (Solanum tuberosum) clones under water stress - Sharma, N.; Kumar, P.; Kadian, M.S.; Pandey, S.K.; Singh, S.V.; Luthra, S.K. (2011)
An experiment was conducted at the Central Potato Research Institute Campus, Modipuram, during autumn crop seasons of 2008 09 and 2009 10, to assess the influence of different irrigation regimes on advanced clones of potato (Solanum tuberosum L.) developed at the International Potato Center, Lima. Three irrigation regimes adopted were: non-stress (five irrigations), moderate water deficit (three irrigations up to 55 days after planting) and severe water deficit (two irrigations up to 25 days after planting). seven clones and two varieties were screened. High canopy temperature was witnessed under reduced irrigation and a difference of 2.1 degree C was recorded between normal irrigated and severe water deficit treatments 80 days after planting. Plant height decreased significantly with reduced irrigation, especially under severe water deficit from 48.3 cm to 35.4 cm. Marketable tubers/plant reduced significantly from 7.2 (normal irrigation regime) to 3.9 (severe water deficit). Tuber yield was also reduced significantly from 560 g/plant (normal irrigation regime) to 271 g/ plant (severe water deficit). Yield reduction under severe water deficit was minimum in CIP clone 397069.11 (39.6%), followed by clone 395195.7 (47.3%). The high yield maintenance ability of clones 395195.7 and 397069.11 under severe water stress was also supported by the higher drought tolerance index (0.983 and 0.566 respectively) and the lower drought susceptibility index (0.914 and 0.729 respectively). Across the clones, tuber dry matter content was higher under severely reduced irrigation (21.9%) compared to normal irrigation (18.9%). Among clones, maximum tuber dry matter content was recorded in clone 395195.7 (22.4%) compared to varieties Kufri Bahar (21.0%) and Kufri Pukhraj (18.2%).